IFRS dan Ketepatan Waktu Pengakuan Laba - Agustina Prativi Nugraheni (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2021)
This study aims to investigate the influence of International Financial Reporting Standards (IFRS) implementation on earning timeliness. Ball and Brown metric is used to examine earning timeliness. This research use Slovin method to determine the number of sample and selection with simple random sampling.The hypothesis tested using regression and chow test. The result show that IFRS hasn’t significantly improve the earning timeliness from before to after IFRS implementation. The reason is earning quality is sensitive to capital market environment and the bearish capital market condition.